(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article describes a study carried out based on the parameters for Research in the Arts according to Henk Borgdorff. Such parameters are presented and put in dialogue with contemporary authors of the Performing Arts in order to point out similarities between them and demonstrate the possibility of dialogue between their conceptions. The study consisted of the mixture of different procedures of scenic practice, carried out in different stages and phases, with the objective of systematizing the process of dramaturgical creation by actors. As a result, two versions of a dramaturgy, a stage performance, an open rehearsal of the performance in progress, and a finished theatrical show were produced. A methodological proposal systematizing the process of dramaturgical creation by actors was also elaborated. The results show that Research in the Arts is configured as a methodological approach that can be adopted by actors/actresses-investigators for practical research.